Comprehensive modeling of optoelectronic nanostructures - Witzigmann, Bernd; Veprek, Ratko G.; Steiger, Sebastian; Kupec, Jan (Journal of Computational Electronics, 2009)
This paper gives an overview of physics-based modeling of optoelectronic nanostructures, driven by diverse applications such as photovoltaics, solid-state lighting, communications and sensing. Despite this broad field of applications, some common challenges can be identified: accurate modeling of light-matter interaction, semi-coherent carrier transport in the presence of strong recombination, calculation of material properties and electromagnetic characteristics. In this contribution, the general purpose simulation framework tdkp/AQUA/LUMI is presented, with the focus on non-planar nanowire devices. © 2009 Springer Science+Business Media LLC.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Light emitting diodes; Optoelectronics; Photovoltaics; Simulation